Inverse problem for semilinear wave equation with strong damping - Protsakh, Nataliya (Frontiers in Applied Mathematics and Statistics, 2024)
The initial-boundary and the inverse coefficient problems for the semilinear hyperbolic equation with the strong damping are considered in this article. The conditions for the existence and uniqueness of solutions in Sobolev spaces for these problems have been obtained. The inverse problem determines the unknown time-dependent parameter in the right-hand side function of the equation with the use of the additional integral type overdetermination condition.